PENGARUH PEMBERIAN ZAT PERANGSANG TUMBUH TERHADAP PERTUMBUHAN BIBIT TANAMAN GAHARU (Aquilaria malaccensis Lamk) DI POLYBAG - Siyamsih, Dwi (Scientica Education Journal, 2024)
This research was carried out in Penginjau Hamlet, Bathin II Pelayang District, Bungo Regency, at an altitude of ± 75 meters above sea level. The research was carried out from 05 January 2015 to 05 April 2015. This research aims to study to determine the effect of giving growth stimulants on the growth of gaharu plant seeds (Aquilaria malaccensis Lamk) in polybags. The aim of the research is to obtain a dose of growth stimulants that will give results to the growth of agarwood seedlings.The method used in this research was a completely randomized design (RAK), with 5 treatments and 4 replications. The concentration of Atonic growth stimulant used was as follows: A0: No treatment (as control), A1: 0.50 cc Atonic ZPT/liter of water , A2: 1.00 cc ZPT Atonik/ liter of water, A3: 1.50 cc ZPT Atonik/ liter of water and A4: 2.00 cc ZPT Atonik/ liter of water. The data obtained from the final observations were analyzed using variance, if they had a real effect then continued with the Duncan New's Multiple Range Test (DNMRT). The variables observed were plant height (cm), total leaf area (cm2), stem diameter (mm) and root volume (ml). From the experimental results, the administration of atonic plant growth regulator (ZPT) concentrations had no significant effect on plant height (cm), total leaf area (cm2), stem circumference (mm) and root volume (ml)